Pembuatan Mesin Pencacah Sampah Organik Untuk Swadaya Pupuk di Desa Tancep Kecamatan Ngawen Kabupaten Gunungkidul - Ignatius Aris Hendaryanto (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2018)
To improve agricultural and plantation yields, farmers need fertilizer. Currently the problems faced by farmers in Tancep Village Ngawen District Gunungkidul Regency is the scarcity and high price of fertilizer. On the other hand, the area has great potential, in the form of availability of organic materials and animal manure that can be utilized as fertilizer. In this community service the knowledge and simple technology to process waste and other organic materials into compost were given. The process of making compost requires the process of chopping garbage or organic materials, such as wet leaves and twigs, so that the pieces are small. For that in this activity needs to be done making garbage chopper machine or organic materials. An organic waste counter machine is made with a rotary blade construction consisting of 12 blades. The construction of a machine is made portable with a propulsion in the form of a gasoline engine, so the machine is easily moved and operated indoors or outdoors. Through community service activities in Tancep Village, Ngawen Subdistrict, Gunungkidul Regency has formed a garbage bank managed by Karang Taruna group. In addition to collecting and reselling of inorganic waste, the activity developed is processing organic waste into compost. Through the knowledge and equipment owned, it is expected that the compost fertilizer produced can help meet the needs of fertilizer for local farmers to self-help fertilizer.